Epidemiological characteristics, virulence genes, and antimicrobial resistance analysis of Vibrio parahaemolyticus in diarrheal cases in Huzhou City from 2021 to 2023 - Wu, Xiaofang; Chen, Liping; Zhu, Xiaojuan; Ji, Lei; Dong, Fenfen (Frontiers in Microbiology, 2025)
Vibrio parahaemolyticus has emerged as a predominant cause of seafood-related infections globally. Despite this, a comprehensive analysis of its epidemiological traits and antimicrobial resistance patterns in Huzhou City remains lacking. Our study isolated 250 strains of V. parahaemolyticus from a total of 6,404 diarrhea patients sampled across six hospitals in Huzhou from 2021 to 2023. Epidemiological analysis revealed higher infection rates in warmer seasons, with the majority of cases occurring in individuals aged from 25 to 64. No significant gender-based difference was observed in the prevalence of V. parahaemolyticus. Serotype analysis identified O10:K4 as the predominant serotype. 93.20% (233/250) of clinical isolates harbored the tdh gene, while 4.0% (10/250) carrying the trh. Antimicrobial sensitivity testing indicated a strikingly high resistance rate of 95.56% (172/180) to cefazolin among clinical isolates. The cgMLST-based minimum spanning tree analysis revealed that the O4:KUT clinical isolates segregated into two distinct clusters, ST3 and ST2516, with considerable evolutionary divergence between them. In contrast, the O10:K4 and O3:K6 serotypes exhibited closer phylogenetic proximity. This study comprehensively characterizes V. parahaemolyticus in Huzhou, revealing critical insights into its epidemiology, virulence factors, and antibiotic resistance patterns, thereby enhancing our knowledge of its public health risks.